A Comprehensive Systematic Review of Investigating the Antioxidant Effect of Vitamin E in Depression - Oktaberika Putri Indah Yasinta; Eka Pramudian Rismayanti (The International Journal of Medical Science and Health Research, 2025)
Introduction: Depression is a prevalent global mental health disorder with a complex, multifactorial pathophysiology. Emerging evidence suggests a significant role of oxidative stress and impaired antioxidant defense in its development and progression. Vitamin E, a potent lipid-soluble antioxidant, has been investigated for its potential therapeutic role in mitigating oxidative damage and alleviating depressive symptoms (Lee et al., 2022; Barbosa et al., 2020). Methods: This comprehensive systematic review synthesized evidence from 14 sources, including randomized controlled trials (RCTs), meta-analyses, and observational studies. Studies were screened and selected based on predefined criteria involving human participants with depression, vitamin E intervention (as monotherapy or co-intervention), measurement of antioxidant biomarkers and depression outcomes, and specific study designs that allowed for the isolation of vitamin E effects. Results: The pooled meta-analysis indicated a moderate beneficial effect of vitamin E supplementation on depression scores (SMD = -0.88, 95% CI: -1.54 to -0.21) (Lee et al., 2022). Observational data showed an inverse association between dietary vitamin E intake and depression risk (RR = 0.84) (Ding & Zhang, 2022). Significant improvements in antioxidant biomarkers, such as increased total antioxidant capacity (TAC) and reduced malondialdehyde (MDA), were consistently reported with vitamin E supplementation, particularly at doses of 400 IU or higher (Farshbaf-Khalili et al., 2022; Darabi et al., 2023). However, effects were more pronounced in populations with elevated oxidative stress (e.g., PCOS, occupational exposure) and when vitamin E was combined with other antioxidants or omega-3 fatty acids. Discussion: The antidepressant effects of vitamin E appear to be mediated through its ability to reduce oxidative stress and lipid peroxidation, modulate inflammatory pathways, and possibly influence gene expression related to neuroprotection (Lee et al., 2022; Almulla et al., 2023). Significant heterogeneity in study outcomes can be attributed to factors such as dosage, formulation, population characteristics, and the common use of vitamin E as a co-intervention. Conclusion: Vitamin E supplementation, particularly at higher doses and in populations with evident oxidative stress burden, may offer a safe and modest adjunctive benefit in the management of depression. Future research should prioritize large-scale, well-designed RCTs of vitamin E monotherapy, with stratified analyses based on baseline antioxidant status, to clarify its independent therapeutic role.